Pengaruh Pembiayaan Modal Kerja Pada Akad Musyārakah Terhadap Profitabiliyas Bank Mumalat Indonesia, Bank Mega Syariah Dan Bca Syariah Periode 2019-2021 - Sari Utami (Economics and Digital Business Review, 2025)
Examining Islamic financial performance using the ROA indicator uses a quantitative approach for its methodology and Islamic finance for its scientific aspects. To realize these two approaches, the Working Capital Financing variable is used as a measure of product purchases in determining the level of profitability of Islamic Commercial Banks. The required data are the amount of Musyarakah Financing, total Financing Results, net profit, and total assets. The data collection technique used in this study is documentation. The documentation used is the financial reports of Islamic Commercial Banks consisting of three banks: Bank Muamalat Indonesia, Bank MEGA Syariah, and BCA Syariah from 2019-2021 through the Financial Services Authority (OJK) website. The results show that the three Islamic Commercial Banks only influence Musyarakah financing variables by 3%, while the other 97% is influenced by several financing variables such as murabahah, salam, istisna', ijarah, qard, current accounts, savings, and deposits. The regression results on REM show that Musyarakah Financing (0.0657) has a positive effect on probability, which is smaller than 0.05. Therefore, Musyarakah financing has an effect on the three BUS (Bank Mumalat, Bank Mega Syariah, and BCA Syariah).